2022
DOI: 10.1186/s12887-022-03626-2
|View full text |Cite
|
Sign up to set email alerts
|

Physical growth and sexual maturation of perinatally HIV-infected adolescent males in a southeast Nigerian tertiary hospital: a comparative cross-sectional study

Abstract: Background The advent of highly-active anti-retroviral therapy (HAART) has resulted in the survival of children with Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) into adolescence. Their prolonged survival has translated into co-morbidities like endocrine deficiencies which may manifest as growth and pubertal delay. This study aimed to determine the physical growth and sexual maturation of perinatally HIV-infected adolescent males and compare them with those of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…This is understandable as HIV infection and the attendant immunosuppression is known to exert a negative effect on the pubertal development process. Similar findings have also been reported in some previous studies [9,20,21].…”
Section: Discussionsupporting
confidence: 92%
“…This is understandable as HIV infection and the attendant immunosuppression is known to exert a negative effect on the pubertal development process. Similar findings have also been reported in some previous studies [9,20,21].…”
Section: Discussionsupporting
confidence: 92%
“…Viral load would have been a better marker of disease control; unfortunately, it was not nancially feasible to do so in this study, and it was not yet widely available as a standard for monitoring treatment effectiveness in the public sector when the study was conducted. Despite good immunological control of HIV infection, stunting remains a major issue in these HIV-infected adolescents (21). Since HIV-infected infants are now beginning treatment early, new studies have shown that stunting is not as prevalent as in this study, where ART was not started in infancy (12).…”
Section: Discussionmentioning
confidence: 52%